Application of Gagge's energy balance model to determine humidity-dependent temperature thresholds for healthy adults using electric fans during heatwaves. (January 2022) - Tartarini, Federico; Schiavon, Stefano; Jay, Ollie; Arens, Edward; Huizenga, Charlie
Abstract: Heatwaves are one of the most dangerous natural hazards causing more than 166, 000 deaths from 1998–2017. Their frequency is increasing, and they are becoming more intense. Electric fans are an efficient, and sustainable solution to cool people. They are, for most applications, the cheapest cooling technology available. However, many national and international health guidelines actively advise people not to use them when indoor air temperatures exceed the skin temperature, approximately 35 °C. We used a human energy balance model, to verify the validity of those recommendations and to determine under which environmental (air temperature, relative humidity, air speed and mean radiant temperature) and personal (metabolic rate, clothing) conditions the use of fans would be beneficial. We found that current guidelines are too restrictive. Electric fans can be used safely even if the indoor dry-bulb temperature exceeds 35 °C since they significantly increase the amount of sweat that evaporates from the skin. The use of elevated air speeds (0.8 m/s) increases the critical operative temperature at which heat strain is expected to occur by an average of 14 °C for relative humidity values above 22 %. We also analyzed the most extreme weather events from 1990 to 2014 recorded in the 115 most populous cities worldwide, and we determined that in 93 of them the use of fans would have been beneficial. We developed a free, open-source, and easy-to-use online tool to help researchers, building practitioners, and policymakers better understand under which conditions electric fans can be safely used to cool people. Graphical abstract: Highlights: Electric fans can safely be used even if the air temperature is higher than 35 °C. Electric fans can cool people even when air temperature exceeds skin temperature. Health guidelines should not discourage people from using fans during heatwaves. Health guidelines regarding the use of electric fans should be reviewed. Our open-source tool calculates humidity-dependent temperature thresholds.